Memory and Absence in Patricio Guzmán’s Chile Trilogy (2010-2019) - Viegas, Susana (Revista de Comunicação e Linguagens, 2025)
This text explores the impossibility of cinematic representations of death through a philosophical approach to the politics of death (thanatopolitics) in Michel Foucault, a useful conceptual tool for analysing Patricio Guzmán’s Chile Trilogy, which comprises Nostalgia de la luz/Nostalgia for the Light (2010), El botón de nácar/The Pearl Button (2015), and La cordillera de los sueños/The Cordillera of Dreams (2019). With no archival footage to document the atrocities and the fate of Chilean dissidents imprisoned and executed under Pinochet’s regime, Guzmán faced a profound challenge: how to create cinematic memories in their absence? Moving images have the power to evoke forgotten and vanished eras, revealing their potential to defy death, oblivion, and absence in a tangible way. Through this approach, Guzmán crafts poetic narratives that seek to mourn, resist amnesia, and confront the (lack of ) knowledge of a collective past.